Japanese art in perspective east-west encounters - Takashina, Shu?ji 1932- (Japan library (Shuppan Bunka Sangyo? Shinko? Zaidan))
How do Japanese and Western aesthetics differ? In this comparative cultural study, TAKASHINA Shu?ji, a leading scholar of Western art history and insightful commentator on Japanese art, compares the two artistic traditions to reveal the distinctive characteristics of the Japanese sense of beauty.